Pengaruh Penggunaan Media Sosial Tiktok terhadap Akhlakul Karimah Peserta Didik Kelas XI di Madrasah Aliyah Ukhuwah Islamiyah Pattallassang - Ruhaya, Besse; Nur Khalisah Latuconsina; Muzakkir; Syamsuri; Rika Ariyani (Inspiratif Pendidikan, 2024)
This study aims to determine the effect of TikTok social media usage on the morals of class XI students at Madrasah Aliyah Ukhuwah Islamiyah Pattallassang. This study is a type of quantitative research with a survey research method. The data sources in this study were students at Madrasah Aliyah Ukhuwah Islamiyah Pattallassang with a sample of 25 students. The research instrument used was a Likert scale to determine the scale of the influence of TikTok social media usage on students' morals. The data analysis techniques used were descriptive statistical analysis and simple linear regression analysis. Based on the results of the descriptive analysis, the results of the study on the use of TikTok social media for class XI students at Madrasah Aliyah Ukhuwah Islamiyah Pattallassang were in the moderate category with a percentage of 68% while the results of the morals of class XI students at Madrasah Aliyah Ukhuwah Islamiyah Pattallassang were in the moderate category, namely 56%. From the results of the significance test, it shows that the TikTok social media usage variable has a negative coefficient value of 0.731, has a t-count value of 3.103 <ttable 1.70, and a significant value of 0.001 <0.05, which means that H1 is accepted while H0 is rejected. This means that there is an influence of the use of TikTok social media on the morals of class XI students at Madrasah Aliyah Ukhuwah Islamiyah Pattallassang